The Financial Technology Investment: A Comparative Analysis of Profitability and Performance in Indonesian State-Owned and Sharia Banks - Widiasmara, Anny; Retnowati, Wulan; Alvarez, Joel I.; De Guzman, Eduardo K. (AKRUAL: JURNAL AKUNTANSI, 2024)
In the digital age, the lack of understanding regarding strategic investments in financial technology within the banking sector emerges as an expensive predicament. This presents a global debate over cost-effectiveness, competitive pressures, intricate bank operations, workforce management, and employee adaptability. This study strives to provide empirical evidence of differences in Return on Asset (ROA), Return on Equity (ROE), Operational Expense to Operational Revenue (BOPO), Net Interest Margin (NIM), Operational Expense Ratio (OPER), and Revenue per Employee (RPE) before and after investing in financial technology within Indonesian Sharia and State-Owned Banks. The results of this research show that for the most part there is no significant difference in the profitability ratios of ROA, ROE, NIM and BOPO, OPER, RPE in Islamic banks but there is a tendency for performance to increase for ROA, ROE, NIM and BOPO, OPER, RPE after collaborating with start -up fintech. In contrast, State-Owned Banks exhibit differences in ROA and BOPO variables before and after such collaborations. The performance metrics of ROA, ROE, and NIM in State-Owned Banks have deteriorated post-collaboration with fintech entities. This calls for caution from the banking sector as it could incur financial losses, negatively impacting operations and overall performance